Mistaking primary hepatic tuberculosis for malignancy: Could surgery have been avoided? - Ghoneim I.; Zuhdi Z.; Arrifin A.C.; Othman H.; Jarmin R.; Azman A. (Elsevier B.V., 2024)
Indexed by WOS/ Scopus